STEM Productive Learning of Lower Secondary School in Southern Zone, Malaysia - Nasir, Mohd Alfouzii; Talib, Rohaya; Latif, Adibah Abdul; Hanid, Mohd Fadzil Abdul; Harmeni, Haiza Atmareni (International Journal of Learning, Teaching and Educational Research, 2023)
Sciences, Technology, Engineering, Mathematics Productive Learning (STEMPL) is an initiative of the Ministry of Education (MoE) to promote creative teaching and learning among STEM teachers, with the ultimate goal of producing students who can think creatively, systematically, and logically in problem-solving. Therefore, this study aims to identify the level of STEMPL practices among STEM teachers in lower secondary schools in the Southern Zone, Malaysia. The differences in STEMPL practices are also examined according to the subjects taught and the relationship of STEMPL practices based on the teaching experiences of the STEM teachers. A survey design was used in this study, applying a quantitative approach. A total of 556 STEM teachers who teach Science, Design and Technology, Computer Science, and Mathematics at the lower secondary level were selected using stratified random sampling techniques. Data were collected using a questionnaire developed by researchers, proven valid and highly reliable for measuring STEMPL practices among STEM teachers. SPSS 23 was used to analyse the data. The findings showed that the overall level of STEMPL practices among STEM teachers were moderate. The analysis also found significant differences in STEMPL practices based on the subjects taught and no significant relationship between STEMPL practices and teaching experience of the STEM teachers. These findings provide input to stakeholders that the STEMPL practices of STEM teachers need improvement in order to realise the education aspirations in Malaysia. Suggestions to improve existing practices are also provided to guide stakeholders in planning, implementing, and evaluating effective strategies.